Pengaruh Good Corporate Governance Dan Corporate Social Responsibility Terhadap Nilai Perusahaan Bumn Go Public Pada Perusahaan Yang Terdaftar Di Bursa Efek Indonesia (BEI) - Nastiti Rizky Shiyammurti; Reny Wahyuni (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research was conducted on publicly traded state-owned companies listed on the Indonesia Stock Exchange for the 2017-2023 period. The aim of this research is to find out how much Good Corporate Governance and Corporate Social Responsibility, either partially or simultaneously, affect the company value of publicly traded state-owned companies listed on the Indonesia Stock Exchange for the 2017-2023 period. The research methods used in this research are descriptive methods and associative methods.In this research, the unit of analysis is financial report documents and sustainability reports on publicly traded state-owned companies listed on the Indonesia Stock Exchange for the 2017-2023 period. The sample in this research was 7 companies. Random sampling is purposive sampling consideration. The analysis method uses multiple linear regression analysis. Based on the research results, it shows that partially there is no significant influence of Good Corporate Governance sub-variables of the board of commissioners, board of directors and audit committee on company value, and partially there is no significant influence of Corporate Social Responsibility on company value.Simultaneously there is an influence of Good Corporate Governance sub variables of the board of commissioners, board of directors, and audit committee and Corporate Social Responsibility on company value. Based on the R Square value obtained at 0.305 or 30.5%, this means that the Good Corporate Governance variable with the sub-variables of the board of commissioners, board of directors and audit committee and the Corporate Social Responsibility variable contributes to the influence on company value of 30.5%, the remaining 69 .5% is influenced by other variables not involved in this research.